Prostate‐specific antigen (PSA) concentrations in hypogonadal men during 6 years of transdermal testosterone treatment. (7th January 2013) - Raynaud, Jean‐Pierre; Gardette, Jean; Rollet, Jacques; Legros, Jean‐Jacques
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Hypogonadism affects an estimated 2–4 million men in the USA, but only 5% receive treatment. Testosterone replacement therapy reduces the effects of testosterone deficiency on sexual function, mood and energy in hypogonadal patients. Long‐term hypogonadism management requires testosterone treatment to restore serum concentrations of testosterone and its active metabolites, within physiological ranges; a testosterone preparation that achieves physiological plasma concentrations without supra‐physiological escape is a preferred option. A previous 1‐year study European clinical study showed the efficacy and safety of a transdermal testosterone patch (Testopatch®). The present study shows the long‐term (6‐year) safety and efficacy of Testopatch in patients with primary or secondary hypogonadism. We show that, over the long‐term, Testopatch was associated with no relevant changes in PSA concentration and PSA velocity, or any significant prostate risks (there were no cases of prostate cancer). Objective To assess the change in prostate‐specific antigen (PSA) concentrations in patients with primary or secondary hypogonadism, receiving transdermal testosterone. Patients and Methods This was an interventional, 6‐year study, conducted in Urology and Endocrinology centres in Belgium, France, Germany, the Netherlands and Spain. Participants were primary (48%) or secondary (52%) hypogonadal patients who received two 60 cm2 testosterone patches (Testopatch®), delivering 4.8 mg of testosterone per day, applied every 2 days. During treatment, total testosterone (TT), dihydrotestosterone, oestradiol and, PSA concentrations were measured in a centralised laboratory every 3 months during the first year, and every 6 months thereafter. Results In all, 200 patients [mean (sd) age 41.0 (12.5) years, body weight 82.5 (13.7) kg, height 177.2 (9.3) cm, body mass index 26.2 (3.4) kg/m2] were treated with transdermal testosterone patches. In all, 161 patients completed the 1‐year study and 115 entered into a 5‐year study extension; 51 patients completed the sixth year of the study. The mean baseline concentrations of TT and PSA were 1.4 ng/mL and 0.47 ng/mL, respectively; TT serum concentrations >3 ng/mL were achieved in 85% of patients and fluctuated between 4.4 and 6.0 ng/mL. At each successive 6‐month time point, mean the PSA values were 0.60, 0.67, 0.76, 0.70, 0.61, 0.68, 0.64, 0.71, 0.75, 0.74, 1.01, 0.78, 0.80 ng/mL, respectively. The mean PSA velocity was negligible (0.00–0.03 ng/mL/year) from 30 months to the end of the trial, except for a value of 0.08 at 60 months. Seven patients had a PSA concentration of >4 ng/mL due to a sharp PSA increase. Six of these patients had prostatitis and PSA concentrations returned to previous levels with appropriate treatment. No prostate cancer was reported during the trial. Conclusion These data support a strong safety profile for Testopatch, even at the highest registered dosage.